KINERJA BIDANG PENGELOLAAN SAMPAH DI DINAS LINGKUNGAN HIDUP DAN KEHUTANAN KABUPATEN SUMEDANG - Dadan Setia Nugraha; Clara Maulida; Indah Sintha; Tatiya Khodyzah; Wilma Juwita; Yulyshya Sartika (LPPM UNSAP & FISIP UNSAP, 2021)
This study aims to determine how the performance of the Sumedang Regency Environment and Forestry Service (DLHK) in management and to find out what are the performance obstacles of the Sumedang Regency Environmental and Forestry Service (DLHK) in waste management. This type of research uses qualitative methods. The population in this study were all employees of the Sumedang Regency Environment and Forestry Service (DLHK) involved in handling waste in the waste management sector, and officers in the field (cleaning task force). Data collection techniques by means of observation, interviews and documentation. Based on this research, it can be concluded that the performance of the Sumedang Regency Environmental and Forestry Service (DLHK) in Waste Management is quite good. This is in accordance with what is stated in the Standard Operating Procedure (SOP) of the Environment and Forestry Service (DLHK) in the field of waste management. The obstacles faced by the Environment and Forestry Service with regard to waste management are the lack of a waste transport fleet and the minimum number of cleaning workers.